The diagnosis of DIC: a current overview - Hongyu Yang; Xiaochun Ma; Xu Li (Frontiers in Medicine)
The name of disseminated intravascular coagulation (DIC) and its diagnostic criteria remain controversial. DIC is a clinical syndrome caused by a variety of etiologies, which determines its high heterogeneity. It is inappropriate to adopt the same diagnostic criteria. DIC has its common characteristics. First, in most DIC, thrombosis and bleeding coexist. Second, DIC is a dynamic process. Third, endothelial cell injury and systemic coagulation activation are the core of DIC. Fourth, DIC is an initiating factor of multiple organ dysfunction syndrome (MODS). There are still controversies about the diagnostic criteria of DIC. First, it relies on clinical manifestations and laboratory tests, which cannot reflect pathophysiology. Second, the clinical manifestations were not sensitive or specific. Third, there is a lack of sensitive biomarkers. Fourth, the parameters in the current diagnostic criteria cannot fully reflect the actual coagulation function. Fifth, it is obviously inappropriate to use the same scoring system for diagnosis of clinical syndromes with different etiologies and pathophysiology. Therefore, it is urgent to re-establish the diagnostic criteria for DIC. In recent years, the understanding of DIC has been continuously improved, including the in-depth understanding of the pathogenesis, the classification of coagulation phenotypes, and the development of the “two-step” diagnosis of DIC, etc. All of these contribute to the establishment of new diagnostic criteria for DIC. In conclusion, it is necessary to develop personalized diagnostic criteria based on etiology, reflecting pathophysiological mechanisms, establishing clear cut-off values for parameters, being clinical applicable, being globally unified, and most importantly, being able to identify therapeutic targets.